Na dobre czy na złe? Wspólny kryzys a dobro wspólne - Michalski, Michał A. (Annales. Etyka w Życiu Gospodarczym, 2013)
Crisis, sometimes associated with historically distant times or centrally planned economies, has turned out to be one of the main contemporary issues. Hence different systems like socialism and capitalism become similar in their inability to reply to expectations for a safe, peaceful and abundant life. It means that economic problems are more complex in their nature.Thorough analysis of the roots of different crises should therefore reach deeper than just economic explanations. This is the point where ethical and cultural explanations may be useful because they strive to explore the socio-cultural fabric at its foundations in the hierarchy of values and vision of human beings and society.When it comes to contemporary crisis the problem is twofold: firstly, there is the threat that the crisis will be treated inadequately and not realistically in consequence. Secondly, the roots ofthe crisis may not be diagnosed properly, which may lead to false ‘treatment’.This article is an attempt to highlight the above issues and analyse them in the context ofthe common good approach, which seems to offer valuable potential to understand the difficulties properly and offer a reasonable plan for recovery.